Pendidikan Vokasi Di Smas Nurul Falaah Desa Cibadung - Mutiara Berta; Edwin Sena Adiana Gatot (STIKes Ibnu Sina Ajibarang, 2024)
Commitment to the community is a real form of the University's contribution to society, industry, local government and community groups struggling for economic and social independence. KKN demands Field Supervisors (DPL) and students to play an active role in recognizing the problems faced before joining the community for one and a half months. With Social Approach is an approach through the process of communication to the student Nurul Falaah Smas to explain the purpose and purpose of devotion, interacting directly with the student in the village cibadung area to introduce members to children and adolescents about the work programme of Vokasi exhibition activities. 18 August 2022 The teaching and learning activities were implemented which began with the introduction of several majors at the Muhammadiyah University of Jakarta. Real Work College (KKN) is an additional activity in the curriculum as a prerequisite for graduation for students. This is also one of the activities in which students truly respect and devote themselves to the tri dharma of the college.